Conjugated polymer covalently modified multi-walled carbon nanotubes for flexible nonvolatile RRAM devices. (5th January 2021) - Gu, Minchao; Zhao, Zhizheng; Liu, Jiaxuan; Liu, Gang; Zhang, Bin; El-Khouly, Mohamed E.; Chen, Yu
Graphical abstract: The as-prepared flexible memory device with a configuration of Al/PDDF- g -MWNTs/ITO-coated polydimethylsiloxane shows typical nonvolatile rewritable memory performance with a higher ON/OFF current ratio of more than 104, a switch-on voltage of +2.07 V and a switch-off voltage of −2.45 V. Highlights: The soluble PDDF- g -MWNTs were successfully synthesized. The as-prepared flexible memory device shows typical nonvolatile rewritable memory performance. The achieved ON/OFF current ratio exceeds more than 10 4 . Electrons dominate the conduct process in PDDF- g -MWNTs. Abstract: Strong demand has been raised for the lightweight, wearable and flexible electronic devices such as wearable computers, paper-like E-readers and epidermal electronics. By using MWNTs-PhBr as a key one dimensional template, novel MWNTs (multi-walled carbon nanotubes) covalently functionalized with poly[(1, 4-diethynyl- benzene)- alt -9, 9-bis-(4-diphenylaminophenyl)fluorene] (PDDF- g -MWNTs), in which the weight percentage of MWNTs is about 22.74, were successfully synthesized. The as-prepared flexible electronic device with a configuration of Al/PDDF- g -MWNTs/ITO-coated polydimethylsiloxane shows typical nonvolatile rewritable memory performance, with a higher ON/OFF current ratio of more than 10 4, a switch-on voltage of +2.07 V and a switch-off voltage of −2.45 V. With increasing the film thicknesses, the ON/OFF current ratio of the device was changed from 1 × 10 4 (80 nm) to 2 × 10 4 (100 nm) to 4 × 10 4 (130 nm). Both the switch-on and switch-off voltages almost kept unchanged even if the film thickness was increased from 80 to 130 nm. Upon bending and stretching, the corresponding electronic device still shows good stability and reliability. Electrons dominate the conduct process in PDDF- g -MWNTs during the operation of the device.